Business model innovation and competitive imitation: The case of sponsor‐based business models - Casadesus‐Masanell, Ramon; Zhu, Feng (Strategic Management Journal, 2013)
Abstract This paper provides the first formal model of business model innovation. Our analysis focuses on sponsor‐based business model innovations where a firm monetizes its product through sponsors rather than setting prices to its customer base. We analyze strategic interactions between an innovative entrant and an incumbent where the incumbent may imitate the entrant's business model innovation once it is revealed. The results suggest that an entrant needs to strategically choose whether to reveal its innovation by competing through the new business model, or conceal it by adopting a traditional business model. We also show that the value of business model innovation may be so substantial that an incumbent may prefer to compete in a duopoly rather than to remain a monopolist. Copyright © 2012 John Wiley & Sons, Ltd.